Dendrophyllia laboreli n.sp., coralliaire infra-litoral et circalitoral de l'Afrique occidentale et des iles Canaries (Cnidaria, Anthozoa, Scleractinia). - Zibrowius, H.; Brito, A. (Bulletin du Museum national d'Histoire naturelle, Paris, 1984)
Dendrophyllia laboreli n. sp., an infralittoral and circalittoral coral from West Africa and the Canary Islands (Cnidaria, Anthozoa, Scleractinia). — D. laboreli forms colonies with closely packed calices on a short common trunk. The colour of the live specimens is due to carotenoids and special bromophenols recognized also in other Dendrophylliids. The species is abundant at the Cap-Vert peninsula, Senegal (type locality) but has also been recorded along the West African coasts from Ghana to West Sahara (24°N) and from the Canary Islands (Fuerteventura, Gran Canaria ; 28°N). It lives on the rocky coast, and off shore on sedimentary bottoms. Various organisms have been found associated with D. laboreli, one of them being the cirriped Megatrema anglicum. Previously D. laboreli had been confused with I). dilatata Van der Horst, 1927, a species of the southwestern Indian Ocean (Mozambique, Natal) ; the latter is redescribed and figured for comparison purposes.